Hereditäres kolorektales Karzinom: effiziente Primärprävention - Kadmon, Martina; Kloor, Matthias; Tariverdian, Mirjam (Der Onkologe, 2012)
Genetically defined hereditary colorectal cancer affects mostly young patients and their families and accounts for approximately 3-5% of all colorectal cancers. Early detection and clinical management determine the prognosis and are the responsibility of clinicians. While the classical variant of familial adenomatous polyposis (FAP) is characterized by a distinct phenotype, Lynch syndrome, attenuated FAP (aFAP) and MUTYH-associated adenomatous polyposis (MAP) show phenotypic overlaps which render unequivocal classification difficult. The present article elucidates the clinical manifestations, current surveillance concepts and preventive operative strategies in patients with hereditary tumor predisposition syndromes and their families.
Gesehen am 07.08.2018
Published online first: 06 July 2011